Molecular diversity of Tamarindus indica clones using Inter Simple Sequence Repeat (ISSR) Markers - Mayavel A; Amaravel M; Akshayasri M; Andrew Peter Leon M.T; Maheswari Patturaj; Sindhu Agasthikumar; Bagathsingh C; Radhakrishnan G; Binai Nagarajan (Tropical Plant Biology, 2026)

Genetic diversity assessment of near-threatened endemic catfish Clarias dussumieri in Western Ghats, India: implications for conservation - Divya Prema Radhakrishnan; Divya Merin Jose; C. P. Abhilash; V. S. Basheer; Uttam Kumar Sarkar (Hydrobiologia, 2026)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

Cellulose as Source and Matrix for Fluorescent Chemo-Sensors - Sicily Rilu Joseph; Jith C. Janardhanan; Sithara Radhakrishnan; Honey John; Ushamani Mythili (Journal of Fluorescence, 2025)

Performance prediction of emulsion treated base layer mixes using indirect tensile strength and resilient modulus test parameters - Jithin Kurian Andrews; Vishnu Radhakrishnan; Reebu Zachariah Koshy; C. S. R. K. Prasad (Innovative Infrastructure Solutions, 2024)

Lyophilized rumen fluid as a ruminal fermentation modifier in high grain-fed acidotic goats - A. Ruba Nanthini; C. Valli; L. Radhakrishnan; D. Balasubramanyam; A. V. Mangalagowri (Tropical Animal Health and Production, 2024)

The critical role of a conserved lysine residue in periplasmic nitrate reductase catalyzed reactions - Nitai C. Giri; Breeanna Mintmier; Manohar Radhakrishnan; Jonathan W. Mielke; Jarett Wilcoxen; Partha Basu (JBIC Journal of Biological Inorganic Chemistry, 2024)

A Histone H2A Derived Antimicrobial Peptide from the Blue Swimmer Crab, Portunus pelagicus Linnaeus 1758: In silico Characterization and Phylogenetic Analysis - V. V. Anooja; P. P. Athira; Kesavan Dhanya; S. Neelima; M. V. Anju; K. Archana; S. Muhammed Musthafa; C. K. Radhakrishnan; Rosamma Philip (Thalassas: An International Journal of Marine Sciences, 2024)

Predicting Human Risk with Multidrug Resistant Enterobacter hormaechei MS2 having MCR 9 Gene Isolated from the Feces of Healthy Broiler Through Whole-Genome Sequence-Based Analysis - Sreejith Sreekumaran; Manjusha Premnath; P. R. Prathyush; Jyothis Mathew; Chitra C. Nath; Nimmy Paul; Swapna Susan Abraham; E. K. Radhakrishnan (Current Microbiology, 2024)

Current approaches, and challenges on identification, remediation and potential risks of emerging plastic contaminants: A review - Huy Hoang Phan Quang; Duc Anh Dinh; Vishal Dutta; Ankush Chauhan; Sudip Kumar Lahiri; C. Gopalakrishnan; Arunkumar Radhakrishnan; Khalid Mujasam Batoo; Lan-Anh Phan Thi (Environmental Toxicology and Pharmacology, 2023)

Critical review of biochemical pathways to transformation of waste and biomass into bioenergy - Sivasubramanian Manikandan; Sundaram Vickram; Ranjna Sirohi; Ramasamy Subbaiya; Radhakrishnan Yedhu Krishnan; Natchimuthu Karmegam; C. Sumathijones; Rajinikanth Rajagopal; Soon Woong Chang; Balasubramani Ravindran; Mukesh Kumar Awasthi (Bioresource Technology, 2023)

Hanging in the air: tree moss diatoms from Indo-Burma biodiversity hot spot of India - C. Radhakrishnan; M. Yogeshwaran; B. Karthick (Aerobiologia, 2022)

Seasonal variation of Caligus rotundigenitalis infestation on the host fish Etroplus suratensis from the Cochin Backwaters, southwest coast of India - N. Jemi Job; A. A. Mohamed Hatha; C. K. Radhakrishnan (Acta Oceanologica Sinica, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Altered functional network connectivity and working memory dysfunction in adolescents with epilepsy - Jennifer Vannest; Rupa Radhakrishnan; Ana M. Gutierrez-Colina; Shari L. Wade; Thomas Maloney; Angela Combs; Luke Turnier; Shelby Merder; Mekibib Altaye; Tzipi-Horowitz-Kraus; Avani C. Modi (Brain Imaging and Behavior, 2021)

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

Hemodynamics mediated epigenetic regulators in the pathogenesis of vascular diseases - C. L. Karthika; S. Ahalya; N. Radhakrishnan; C. C. Kartha; S. Sumi (Molecular and Cellular Biochemistry, 2021)

Genome-based trait prediction in multi- environment breeding trials in groundnut - Manish K. Pandey; Sunil Chaudhari; Diego Jarquin; Pasupuleti Janila; Jose Crossa; Sudam C. Patil; Subramaniam Sundravadana; Dhirendra Khare; Ramesh S. Bhat; Thankappan Radhakrishnan; John M. Hickey; Rajeev K. Varshney (Theoretical and Applied Genetics, 2020)
Key message Comparative assessment identified naïve interaction model, and naïve and informed interaction GS models suitable for achieving higher prediction accuracy in groundnut keeping in mind the high genotype × environment interaction for complex traits. Abstract Genomic selection (GS) can be an efficient and cost-effective breeding approach which captures both small- and large-effect genetic factors and therefore promises to achieve higher genetic gains for complex traits such as yield and oil content in groundnut. A training population was constituted with 340 elite lines followed by genotyping with 58 K ‘Axiom_Arachis’ SNP array and phenotyping for key agronomic traits at three locations in India. Four GS models were tested using three different random cross-validation schemes (CV0, CV1 and CV2). These models are: (1) model 1 (M1 = E + L) which includes the main effects of environment (E) and line (L); (2) model 2 (M2 = E + L + G) which includes the main effects of markers (G) in addition to E and L; (3) model 3 (M3 = E + L + G + GE), a naïve interaction model; and (4) model 4 (E + L + G + LE + GE), a naïve and informed interaction model. Prediction accuracy estimated for four models indicated clear advantage of the inclusion of marker information which was reflected in better prediction accuracy achieved with models M2, M3 and M4 as compared to M1 model. High prediction accuracies (> 0.600) were observed for days to 50% flowering, days to maturity, hundred seed weight, oleic acid, rust@90 days, rust@105 days and late leaf spot@90 days, while medium prediction accuracies (0.400–0.600) were obtained for pods/plant, shelling %, and total yield/plant. Assessment of comparative prediction accuracy for different GS models to perform selection for untested genotypes, and unobserved and unevaluated environments provided greater insights on potential application of GS breeding in groundnut.

Drought tolerant bacterial endophytes with potential plant probiotic effects from Ananas comosus - Aswathy Jayakumar; Pooja Padmakumar; Indu C. Nair; E. K. Radhakrishnan (Biologia, 2020)

Drought-tolerant and plant growth-promoting endophytic Staphylococcus sp. having synergistic effect with silicate supplementation - Aswathy Jayakumar; Arathy Krishna; Indu C. Nair; E. K. Radhakrishnan (Archives of Microbiology, 2020)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Translational genomics for achieving higher genetic gains in groundnut - Manish K. Pandey; Arun K. Pandey; Rakesh Kumar; Chogozie Victor Nwosu; Baozhu Guo; Graeme C. Wright; Ramesh S. Bhat; Xiaoping Chen; Sandip K. Bera; Mei Yuan; Huifang Jiang; Issa Faye; et al. (Theoretical and Applied Genetics, 2020)
Key message Groundnut has entered now in post-genome era enriched with optimum genomic and genetic resources to facilitate faster trait dissection, gene discovery and accelerated genetic improvement for developing climate-smart varieties. Abstract Cultivated groundnut or peanut ( Arachis hypogaea ), an allopolyploid oilseed crop with a large and complex genome, is one of the most nutritious food. This crop is grown in more than 100 countries, and the low productivity has remained the biggest challenge in the semiarid tropics. Recently, the groundnut research community has witnessed fast progress and achieved several key milestones in genomics research including genome sequence assemblies of wild diploid progenitors, wild tetraploid and both the subspecies of cultivated tetraploids, resequencing of diverse germplasm lines, genome-wide transcriptome atlas and cost-effective high and low-density genotyping assays. These genomic resources have enabled high-resolution trait mapping by using germplasm diversity panels and multi-parent genetic populations leading to precise gene discovery and diagnostic marker development. Furthermore, development and deployment of diagnostic markers have facilitated screening early generation populations as well as marker-assisted backcrossing breeding leading to development and commercialization of some molecular breeding products in groundnut. Several new genomics applications/technologies such as genomic selection, speed breeding, mid-density genotyping assay and genome editing are in pipeline. The integration of these new technologies hold great promise for developing climate-smart, high yielding and more nutritious groundnut varieties in the post-genome era.

Highs and lows of cannabinoid-dopamine interactions: effects of genetic variability and pharmacological modulation of catechol-O-methyl transferase on the acute response to delta-9-tetrahydrocannabinol in humans - Mohini Ranganathan; Joao P. De Aquino; Jose A. Cortes-Briones; Rajiv Radhakrishnan; Brian Pittman; Savita Bhakta; Deepak C. D’Souza (Psychopharmacology, 2019)

Plant Growth Enhancement, Disease Resistance, and Elemental Modulatory Effects of Plant Probiotic Endophytic Bacillus sp. Fcl1 - Aswathy Jayakumar; Arathy Krishna; Mahesh Mohan; Indu C. Nair; E. K. Radhakrishnan (Probiotics and Antimicrobial Proteins, 2019)

Biogenic Gold Nanoparticle Supplementation to Plant Beneficial Pseudomonas monteilii was Found to Enhance its Plant Probiotic Effect - Jishma Panichikkal; Roshmi Thomas; Jimtha C. John; E. K. Radhakrishnan (Current Microbiology, 2019)

Chemicobiological Insight into Anti-phytopathogenic Properties of Rhizospheric Serratia plymuthica R51 - C. Jimtha John; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Multipotent Plant Probiotic Rhizobacteria from Western Ghats and Its Effect on Quantitative Enhancement of Medicinal Natural Product Biosynthesis - C. John Jimtha; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Endophytic Paraconiothyrium sp. from Zingiber officinale Rosc. Displays Broad-Spectrum Antimicrobial Activity by Production of Danthron - C. Anisha; P. Sachidanandan; E. K. Radhakrishnan (Current Microbiology, 2018)

DNAzyme Based Amplified Biosensor on Ultrasensitive Fluorescence Detection of Pb (II) Ions from Aqueous System - A. Ravikumar; P. Panneerselvam; K. Radhakrishnan; Norhashimah Morad; C. D. Anuradha; S. Sivanesan (Journal of Fluorescence, 2017)

Photochemical Degradation of Curcumin: a Mechanism for Aqueous Based Sensing of Fluoride - Roopa Venkataraj; C. P. Girijavallabhan; P. Radhakrishnan; V. P. N. Nampoori; M. Kailasnath (Journal of Fluorescence, 2017)

Effects of Probiotics on Survival, Growth and Digestive Enzymes Activities in Freshwater Prawn Macrobrachium rosenbergii (De Man 1879) - C. Seenivasan; S. Radhakrishnan; T. Muralisankar; P. Saravana Bhavan (Proceedings of the Zoological Society, 2016)

Phytostimulatory and hardening period-reducing effects of plant-associated bacteria on micropropagated Musa acuminata cv. Grand Naine - E. P. Suada; B. Jasim; C. J. Jimtha; G. P. Gayatri; E. K. Radhakrishnan; A. Remakanthan (In Vitro Cellular & Developmental Biology - Plant, 2015)

Influence of Probiotics on Survival, Growth, Biochemical Changes and Energy Utilization Performance of Macrobrachium rosenbergii Post-larvae - C. Seenivasan; S. Radhakrishnan; R. Shanthi; T. Muralisankar; P. Saravana Bhavan (Proceedings of the Zoological Society, 2015)

Marker-assisted introgression of a QTL region to improve rust resistance in three elite and popular varieties of peanut (Arachis hypogaea L.) - Rajeev K. Varshney; Manish K. Pandey; Pasupuleti Janila; Shyam N. Nigam; Harikishan Sudini; M. V. C. Gowda; Manda Sriswathi; T. Radhakrishnan; Surendra S. Manohar; Patne Nagesh (Theoretical and Applied Genetics, 2014)

Isolation of endophytic bacteria from embryogenic suspension culture of banana and assessment of their plant growth promoting properties - John C. Jimtha; P. V. Smitha; C. Anisha; Thomas Deepthi; George Meekha; E. K. Radhakrishnan; G. P. Gayatri; A. Remakanthan (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Phenazine carboxylic acid production and rhizome protective effect of endophytic Pseudomonas aeruginosa isolated from Zingiber officinale - B. Jasim; C. Anisha; Sabu Rohini; Jacob Manoj Kurian; Mathew Jyothis; E. K. Radhakrishnan (World Journal of Microbiology and Biotechnology, 2014)

Influence of medicinal herbs (Alteranthera sessilis, Eclipta alba and Cissus quadrangularis) on growth and biochemical parameters of the freshwater prawn Macrobrachium rosenbergii - S. Radhakrishnan; P. Saravana Bhavan; C. Seenivasan; R. Shanthi; R. Poongodi (Aquaculture International, 2014)

UV-Visible Photoluminescence of TiO2 Nanoparticles Prepared by Hydrothermal Method - S. Mathew; Amit kumar Prasad; Thomas Benoy; P. P. Rakesh; Misha Hari; T. M Libish; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2012)

Identification of hot spots and well managed areas of Pichavaram mangrove using Landsat TM and Resourcesat—1 LISS IV: an example of coastal resource conservation along Tamil Nadu Coast, India - T. Srinivasa Kumar; R. S. Mahendra; Shailesh Nayak; K. Radhakrishnan; Kali C. Sahu (Journal of Coastal Conservation, 2012)

Anti-inflammatory activities of aqueous/ethanol and methanol extracts of Perna viridis Linn. in mice - K. L. Sreejamole; C. K. Radhakrishnan; J. Padikkala (Inflammopharmacology, 2011)

Shifting of Fluorescence Peak in CdS Nanoparticles by Excitation Wavelength Change - S. Mathew; Santhi Ani Joseph; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2011)

Identification of several small main-effect QTLs and a large number of epistatic QTLs for drought tolerance related traits in groundnut (Arachis hypogaea L.) - K. Ravi; V. Vadez; S. Isobe; R. R. Mir; Y. Guo; S. N. Nigam; M. V. C. Gowda; T. Radhakrishnan; D. J. Bertioli; S. J. Knapp; R. K. Varshney (Theoretical and Applied Genetics, 2011)

Leaf-eating caterpillar ( Opisina arenosella)-induced yield loss in coconut palm - Chandrika Mohan; C.P. Radhakrishnan Nair; C. Kesavan Nampoothiri; P. Rajan (International Journal of Tropical Insect Science, 2010)

Control of the coconut pest Oryctes rhinoceros L. using the Oryctes virus - Murali Gopal; Alka Gupta; B. Sathiamma; C. P. Radhakrishnan Nair (International Journal of Tropical Insect Science, 2001)